2D material–based surface plasmon resonance biosensors for applications in different domains: an insight - Yadav P.K.; Kumar A.; Upadhyay S.; Kumar A.; Srivastava A.; Srivastava M.; Srivastava S.K. (My University, 2025)
The design of surface plasmon resonance (SPR) sensors has been greatly enhanced in recent years by the advancements in the production and integration of nanostructures, leading to more compact and efficient devices. There have been reports of novel SPR sensors having distinct nanostructures, either as signal amplification tags like gold nanoparticles (AuNPs) or as sensing substrate-like two-dimensional (2D) materials including graphene, transition metal dichalcogenides (TMDCs), MXene, black phosphorus (BP), metal-organic frameworks (MOFs), and antimonene. Such 2D-based SPR biosensors offer advantages over conventional sensors due to significant increases in their sensitivity with a good figure of merit and limit of detection (LOD). Due to their atomically thin structure, improved sensitivity, and sophisticated functionalization capabilities, 2D materials can open up new possibilities in the field of healthcare, particularly in point-of-care diagnostics, environmental and food monitoring, homeland security protection, clinical diagnosis and treatment, and flexible or transient bioelectronics. The present study articulates an in-depth analysis of the most recent developments in 2D material–based SPR sensor technology. Moreover, in-depth research of 2D materials, their integration with optoelectronic technology for a new sensing platform, and the predicted and experimental outcomes of various excitation approaches are highlighted, along with the principles of SPR biosensors. Furthermore, the review projects the potential prospects and future trends of these emerging materials-based SPR biosensors to advance in clinical diagnosis, healthcare biochemical, and biological applications. Graphical abstract: (Figure presented.) © The Author(s), under exclusive licence to Springer-Verlag GmbH Austria, part of Springer Nature 2024.